Nanometric diamond delta doping with boron. Issue 1 (7th December 2016) - Butler, James E.; Vikharev, Anatoly; Gorbachev, Alexei; Lobaev, Mikhail; Muchnikov, Anatoly; Radischev, Dmitry; Isaev, Vladimir; Chernov, Valerii; Bogdanov, Sergey; Drozdov, Mikail; Demidov, Evgeniy; Surovegina, Ekaterina; et al.
Abstract : Diamond is desired for active semiconducting device because of it high carrier mobility, high voltage breakdown resistance, and high thermal diffusivity. Exploiting diamond as a semiconductor is hampered by the lack of shallow dopants to create sufficient electronic carriers at room temperature. In this work, nanometer thick, heavily boron doped epitaxial diamond 'delta doped' layers have been grown on ultra smooth diamond surfaces which demonstrate p type conduction with enhanced Hall mobilities of up to 120 cm 2 /Vs and sheet carrier concentrations to 6 × 10 13 cm –2, thus enabling a new class of active diamond electronic devices. (© 2016 WILEY‐VCH Verlag GmbH &Co. KGaA, Weinheim) Abstract : At room temperature, a high mobility two‐dimensional charge conduction layer is formed adjacent to a heavily boron doped, nanometer thick boron doped layer in high quality diamond.